Da expressão que espanta ao toque que encanta: a Calatonia e a Shantala como instrumentos de intervenção no re-significar das relações entre mães e filhos - Ferreira, Maria de Fátima Camargo Dias (2006)
When the affection and the envolvement are transmitted by touch with these meanings, beyond the provisions of security through the satisfaction, that is the way the touch will start to be associated. The understanding of the touch between mother and son promoves conditions to analyze the quality of the relation between both. The objective of this work is to understand the importance of touch in the relations between mother and son. This work is about a qualitative research were used a case study method. The instruments for this study had been: half-structuralized interview, two sections of Shantala and intercalated between these sessions, four sessions of Calatonia in each mother and four sessions of returnable. To develop the analise interview was used the contents mother narratives, and the contents had been interpreted based in the analytical psychology pressupposed. In the case of Shantala s sessions we construct an instrument of analised comment that before being applied, was submited it to a group of four psychology doctor s, expert in area to validate the consistency and adequacy. The group participant were indicated by the Conselho Tutelar de Taubaté, Taubaté s Fórum Judicial District and the Clinic of Psychology of the University Taubaté. The children complains were situations of negligence and maltreatment. The number of participants in the research was four mothers with five years old lesser children, only one of the them had three lesser children under five years and the others had one child. The results, had disclosed between the first session and the second session of Shantala and had changed on the mothers attitudes in the application the massage on their children. In the first session they met anxious and tense, and in the second session they had demonstrated tranquillity. As well as had a different reaction in the children between first and the second session of Shantala, they demonstrated more acceptance and envolvement with their mothers. The results suggests that when the mothers also were submitted to the corporal touch technique, that in case was the Calatonia, had a expressive and positive modification in their attitudes in relation to their children, causing the importance of intervension procced in the touch